Ecological Boarding School: Environment-Based Character Education - Khosim, Mokhammad; Mas’adah, Ni’mah Lailatul (Risalatuna Journal of Pesantren Studies, 2025)
This study aims to explore the implementation of environment-based character education at Pondok Pesantren As-Syarify Lumajang and its impact on students’ ecological awareness. The research is grounded in the critical role of pesantren in shaping a generation that is not only religiously knowledgeable but also environmentally conscious. By integrating Islamic values with environmental conservation principles, As-Syarify is committed to fostering an eco-friendly learning environment. A descriptive qualitative approach was employed, with data collected through in-depth interviews, direct observation, and document analysis related to the eco-pesantren program. The research involved the pesantren leadership, educators, and students as respondents, aiming to comprehensively understand the implementation of environment-based character education and the students’ behaviors in preserving nature. The findings indicate that the eco-pesantren program effectively cultivates students’ ecological awareness, enhances environmentally friendly behaviors, and fosters a sense of responsibility for environmental preservation. Students actively participate in reforestation activities, waste management, and the prudent use of natural resources.